Thermodynamics of a Bose gas: Sound velocity from global variables and equivalence with other approaches - Fritsch, Amilson Rogelso (2016)
In this thesis we present some studies that were done in a trapped 87Rb Bose-Einstein condensate using the thermodynamic global variables. We have measured the global sound velocity by studying the variation of the total number of trapped atoms as a function of temperature. This method allowed us to determine the contribution of thermal and BEC components at each temperature. In order to study the sound velocity in each component, we treated both fluids as they were completely independent and we found great similarity with a published work. In addition, we analyze theoretically the validity of the global variables by comparing this approach with other methods. The specific heat for an ideal gas was evaluated using the global variables and by using the usual statistical approach found in textbooks. After finding the same result for both methods, we used the simplicity to implement the interaction in the global approach, to study the variation in the specific heat when the interactions are taken into account. The last comparison was done between global variables and the local density approximation. We have obtained that, for the isothermal compressibility and a equation of state, both methods provide equivalent results.